Cognitive Impairment in Celiac Disease Patients: Scoping Review Exploring Psychological Triggers in a Chronic Condition - Alberto Caruso; Dina Di Giacomo (Gastrointestinal Disorders, 2023)
Celiac disease (CD), also known as gluten-sensitive enteropathy, is an inflammatory autoimmune reaction triggered by ingestion of gluten in genetically predisposed subjects. Celiac disease is often associated with a wide range of disorders, caused by immune responses and by malabsorption with subsequent nutritional deficiencies. Prevalent neurologic manifestations are ataxia, epilepsy, cerebral calcification, cerebral white matter lesions, peripheral neuropathy and myopathy, but also cognitive impairment. The study aimed to identify emerging and urgent research domains in order to establish a CD-specific patient-tailored protocol that includes both psychological and neuropsychological evaluations. We performed a systematic search of MEDLINE, PubMed, SCOPUS, Web of Science and Cochrane library in November 2022. We conducted a descriptive analysis of the characteristics of the included literature. Based on the exclusion/inclusion criteria, a total of seven articles were included in the scoping review process. This review demonstrated the lack of research on CD-related cognitive impairment key features and tries to focus on both cognitive and psychological manifestations as well as their two-way interaction. We tried to establish the specific areas involved, in order to have a comprehensive view of this condition and trying to determine a correct way of assessing CD cognitive impairment and its correlations with psychological distress and personal coping skills to a chronic condition. Nevertheless, research on this topic is progressively increasing and future studies should address specific key points.